2016
DOI: 10.1103/physrevb.93.205411
|View full text |Cite
|
Sign up to set email alerts
|

Efficient quantum modeling of inelastic interactions in nanodevices

Abstract: International audienceThis paper presents an efficient direct quantum method to model inelastic scattering in nanoelectronic structures including degenerate band extrema. It couples the Born series expansion of the nonequilibrium Green's function (NEGF) to an analytic continuation based on the Pade approximant technique. Using a two-band k . p Hamiltonian, we analyze the electron transport through a linear chain in the presence of both optical and acoustic phonons. Results are consistently compared with the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…However, it was also shown that the spectral currents built by the 1st LOA Green's function are very far from the SCBA results since only the first order in the interaction was included. In References [31,32], it was shown that, by using the term ∆g 1 = g 0 Σ[g 0 ]g 0 from Equation (6) as a basic building block, the generalized LOA expansion series can be built as…”
Section: Lowest Order Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was also shown that the spectral currents built by the 1st LOA Green's function are very far from the SCBA results since only the first order in the interaction was included. In References [31,32], it was shown that, by using the term ∆g 1 = g 0 Σ[g 0 ]g 0 from Equation (6) as a basic building block, the generalized LOA expansion series can be built as…”
Section: Lowest Order Approximationmentioning
confidence: 99%
“…The overall schematic of practical calculations for the LOA Green's function g N , which was explained in Reference [32] in detail, is summarized in Algorithm 1 below.…”
Section: Lowest Order Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, calculations of the scattering self-energies and the interacting Green's functions usually rely on a self-consistent scheme called the "self-consistent Born approximation" (SCBA). Alternative direct (i.e., not self-consistent) techniques [12][13][14][15] have been recently developed to calculate the scattering self-energies, but for the sake of clarity, they will not be addressed in this special issue.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the computational cost of inelastic, compared to elastic, device simulations has therefore been an important and unsolved challenge for decades since the first ultrascaled transistors emerged. In the extreme limit of molecular-scale devices there are accurate first-principles methods for inelastic processes available [2][3][4][5][6][7][8][9][10][11][12][13], while in the opposite bulk continuum limit, deformation potentials (DPs) are extracted for Boltzmann transport equations (BTEs) that accurately describe low bias transport [14][15][16][17]. However, in between these two regimes efficient computational methods are missing.…”
mentioning
confidence: 99%